Intramolecular Regulation of the Sequence-Specific mRNA Interferase Activity of MazF Fused to a MazE Fragment with a Linker Cleavable by Specific Proteases - Park, Jung-Ho (American Society for Microbiology, 2012)
The genomes of human immunodeficiency virus type 1 (HIV-1) and hepatitis C virus (HCV) consist of single-stranded RNA encoding polyproteins, which are processed to individual functional proteins by virus-encoded specific proteases. These proteases have been used as targets for drug development. Here, instead of targeting these proteases to inhibit viral infection, we utilized the protease activity to activate a toxic protein to prevent viral infection. We engineered the MazE-MazF antitoxin-toxin system of Escherichia coli to fuse a C-terminal 41-residue fragment of antitoxin MazE to the N-terminal end of toxin MazF with a linker having a specific protease cleavage site for either HIV PR (HIV-1 protease), NS3 protease (HCV protease), or factor Xa. These fusion proteins formed a stable dimer (instead of the MazF(2)-MazE(2)-MazF(2) heterohexamer in nature) to inactivate the ACA (sequence)-specific mRNA interferase activity of MazF. When the fusion proteins were incubated with the corresponding proteases, the MazE fragment was cleaved from the fusion proteins, releasing active MazF, which then acted as an ACA-specific mRNA interferase cleaving single-stranded MS2 phage RNA. The intramolecular regulation of MazF toxicity by proteases as demonstrated may provide a novel approach for preventive and therapeutic treatments of infection by HIV-1, HCV, and other single-stranded RNA viruses.